OPTIMUM TILT ANGLE FOR MAXIMIZING LARGE SCALE SOLAR ELECTRICAL ENERGY OUTPUT (Jurnal Teknologi (Sciences & Engineering), 2021)
Many large-scale solar (LSS) plants that are being installed today have solar photovoltaic (PV) panels mounted on fixed structures, which limits its electrical energy production. Tracking system can be installed so that the PV panels could change its tilt angle automatically in accordance with the sun’s movement. However, it will increase the construction, operation and maintenance cost significantly. Another option is to manually adjust the tilt angle on periodically basis, but the time period and the optimum tilt angle need to be systematically determined. This paper investigates the impact of using monthly and seasonal optimum tilt angle, βopt on electrical energy production of LSS plant. The proposed strategy can be implemented by using tiltable solar panel mounting structures which is far cheaper than the tracking system. For the study, 1 MW LSS system model is used. Twelve cities around the globe with latitude angle ranging from 0º to 55º are strategically selected. The electrical energy output from the 1 MW LSS plant is simulated by using PV mathematical model that is developed in Matlab software. The overall results show that by adjusting the tilt angle of the PV modules into its optimum angle on monthly or seasonal basis, it would increase the generated energy output between 1.91% and 7.24% for monthly adjustments and between 1.59% and 6.06% for seasonal adjustments.